Cheetahs discriminate familiar and unfamiliar human voices. Issue 1 (December 2018) - Leroux, Maël; Hetem, Robyn; Hausberger, Martine; Lemasson, Alban
Abstract Domestic species can make the distinction between several human sub-groups, especially between familiar and unfamiliar persons. The Domestication hypothesis assumes that such advanced cognitive skills were driven by domestication itself. However, such capacities have been shown in wild species as well, highlighting the potential role of early experience and proximity with humans. Nevertheless, few studies have been focusing on the use of acoustic cues in wild species and more comparative studies are necessary to better understand this ability. Cheetah is a vocal, semi-social species, often hand raised when captive, making it therefore a good candidate for studying the ability to perceive differences in human voices. In this study, we used playback experiments to investigate whether cheetahs are able to distinguish between the voices of their familiar caretakers and visitors. We found that cheetahs showed a higher visual attention, changed activity more often and faster when the voice was familiar than when it was unfamiliar. This study is the first evidence that wild felids are able to discriminate human voices and could support the idea that early experience and proximity to humans are at least as important as domestication when it comes to the ability to recognize humans.